TINJAUAN FIKIH SIYASAH TERHADAP PERANAN SATPOL PP DALAM MENGIMPLEMENTASIKAN SURAT EDARAN WALIKOTA NO. 497/ SATGAS COVID-19 TAHUN 2021 TENTANG PELAKSANAAN PPKM DI PADANGSIDIMPUAN - Puji Kurniawan (IAIN Padangsidimpuan, 2021)
The Civil Service Police Unit is an apparatus or local government apparatus that enforces Regional Regulations and maintains peace and public order for the community, so that the community can carry out activities in an orderly, peaceful and orderly manner. One of the duties and authorities of the Civil Service Police Unit is to implement micro-based community activity restrictions (PPKM) in Padangsidimpuan City.